Emulator for adjusting and improving the management program of multitasks of AFC/PFC analyzer Clarke Hess 250 - Ishchenko, Liubomyr; Baran, Mariana (Видавництво Львівської політехніки, 2020)
Nowadays, digital technologies are successful in many areas substantially facilitating the lives of people. Different kinds of computers with special software are applied to manage devices. But the choice of an appropriate program is quite difficult. There the certain error not predicted previously at the stage of the software development may arise. For debugging this type of application, the physical device is needed. The latter may not be available due to its usage by other specialists. To solve such problems, the emulators that simulate the work of a particular system are developed. An article presents the problem of operating the control program multifunction gainphase analyzer of Clarke Hess 2505 with calibrating coil system. The development strategy for its debugging is created and an emulator for debugging the gain-phase analyzer control program is implemented. It allows the leading engineer to establish the program operation, stability, and resistance to various problems.
Keywords: Emulator; Debugging program; Calibration system of magnetometers